(untitled) (Web of Teachers: Inderscience Research, 2024)
The issue of the relationship between the language and culture is always in the spotlight of scientists (V.Gumboldt, E. Sej N.F. Alefiro, N.Afanaseva, Yu.A. Sarokinin, Yu.I. Koltsova and b.). According to the E.Speer, the language is closely linked to culture, expresses it, and the culture serves as a basis for the development of culture [Sepir E. Izbrannye Trudy Po Yazykoznaniyu i Kulthurology. - m.: Progress, 1993. - S. 223.].